Konseling Adlerian: Tinjauan Filosofis - Habsy, Bakhrudin All; Mubarok, Alfi Kamelia; Saputri, Warnanda Eka; Firdaus, Musyaffa Dafa (Lembaga Yasin AlSys, 2024)
Alfred Adler was a major contributor to the psychodynamic approach to therapy. He believed that humans are the creators of their own lives and develop a unique lifestyle that is an expression of their chosen purpose. Humans choose their own path in life, this theory is called adlerian counseling. By using a quantitative method of literature study approach sourced from articles and journals. So that the results obtained (1) Biography of Adlerian Counseling figures (2) Definition of counseling (3) Purpose of Adlerian Counseling (4) Roles and functions of counselors according to Adlerian (5) Experience of counselees in Adlerian counseling (6) Relationship between counselors and adlerian counselees.